Advanced corrosion resistant cylinder-bore coatings. Issue 1 (May 2021) - Schilder, B; Garling, A; Mayer, U; Grabs, R; Lampke, T
Abstract: This paper presents a novel approach to enhance the corrosion resistance of cylinder-bore coatings for internal combustion engines by changing surface characteristics and microstructures of the coating and utilizing alternative materials. The approach of this study refers to the knowledge of the complex gas-flow conditions during the internal-diameter coating of cylinder-bores using a twin-wire arc-spray process. Selective influencing of the gas flow enables the preparation of sample coatings with inhomogeneous and more homogeneous microstructures and surfaces. The various coatings were exposed to corrosive environments using the Kesternich testing method and an alternating immersion test. Significant improvements in corrosion resistance have been demonstrated by up to 50 % through altering the microstructure of the coating and almost 100 % by additional changing the spraying material. The study reveals an increased protection of cylinder-bore coatings against corrosive attacks through a homogeneous microstructure prepared in oxygen-poor coating conditions.